Access, Lifelong Learning and Education for All - Parry, Gareth; Osborne, Michael; Scott, Peter (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"The time is ripe for re-evaluation of access, lifelong learning and education for all in the light of contemporary social and ecological perspectives. This book lays the ground for this critical examination. The three different but intersecting and overlapping domains are explored conceptually and in practice across educational sectors and continents. It is a thought-provoking text by serious scholars." - Shirley Walters, University of the Western Cape, South Africa "This insightful collection is a must-read for scholars, students and policy-makers. With its broad geographical spread and wide-ranging examples, many rooted in practice, the collection opens up new and constructive ways of thinking about access, lifelong learning and education for all." - Miriam Zukas, Birkbeck, University of London, UK "This volume explores the wide-ranging demands confronting post-secondary education. Drawing on experience in a variety of international settings, the issues for governments, organisations, communities and individuals are considered. The volume will be a key resource for researchers and decision-makers." - John Field, University of Stirling, UK This book examines access, lifelong learning and education for all, which have been policy preoccupations in all countries for more than half a century, but have been overlaid and pushed aside by the development of mass higher education. The authors examine what has been achieved, what lessons have been learnt and what still remains to be done, addressing matters of equity, agency, community, mobility and hierarchy. Gareth Parry is Professor Emeritus at the University of Sheffield, UK, where he was Director of the Centre for the Study of Higher Education. Michael Osborne is Professor of Adult and Continuing Education at the University of Glasgow, UK, where he is Director of the Centre for Research and Development in Adult and Lifelong Learning. Peter Scott is Emeritus Professor of Higher Education Studies at the Institute of Education, University College London, UK, and was Scotland's Commissioner for Fair Access.
Contents 1 Introduction -- Part I Access Beyond Elites -- Chapter 2 Access, Equity and Widening Participation -- Chapter 3 Human Capital Theory and Its Discontents -- Chapter 4 Adult and Lifelong Learning Epistemologies in Africa -- Chapter 5 Widening Access to Higher Education: Changing Demographics, Overcoming Old Barriers and the Role of Lifelong Learning -- Part II Alternative Pathways -- Chapter 6 Beyond the Segmentation Between Vocational Training and Higher Education: New Qualification Pathways in Germany -- Chapter 7 Community Colleges in the United States: Navigating Multiple Missions During Uncertain Times -- Chapter 8 The Alternative Route Revisited -- Chapter 9 Higher Level Vocational Qualifications as Pathways to Work and Further Study -- Part III Learning in Community Settings -- Chapter 10 Partial Inclusions: Smart Cities, Labour Market and Educational Opportunities in India -- Chapter 11 Community Learning Centres in the Asia Region: Popular Education and Community Transformation -- Chapter 12 Learning Outside the Academy: Conceptual Debates and Research Challenges -- Chapter 13 Relations in Learning and Research: The Case of the Centre for Research in Lifelong Learning.
Keywords: Continuing education; Education, Higher; Professional education; Vocational education; Lifelong Learning; Higher Education; Professional and Vocational Education